أهمية نظم المعلومات المحاسبية في عملية اتخاذ القرارات بالمؤسسة الإقتصادية _ دراسة ميدانية _ - ياسر قية; عبد النور حمايتي; هنادي محلو; امل مساوي (جامعة الوادي university of eloued, 2024)
"تهدف هذه الدراسة إلى معرفة كيفية مساهمة نظم المعلومات المحاسبية في تحسين عملية اتخاذ القرار وذلك من خلال التعرف على نظم المعلومات المحاسبية وجميع أجزاءها مرورا بعملية اتخاذ القرار ووصولا إلى كيفية مساهمة نظم المعلومات المحاسبية ودورها في تحسين مراحل عملية اتخاذ القرارات في المؤسسة الاقتصادية. ومن أهم النتائج المتوصل إليها هو أن نظم المعلومات المحاسبية تمثل ذلك الجزء الأساسي والهام من نظم المعلومات الإدارية في المؤسسات الاقتصادية والتي هي بدورها تقوم بتجميع البيانات المالية المختلفة من مصادر خارج وداخل المؤسسة ثم تقوم بتشغيل هذه البيانات وتحويلها إلى معلومات مالية مفيدة لاتخاذ القرارات وتوفيرها للمستخدمين الداخلين والخارجين للمؤسسة، وتعتبر نظم المعلومات المحاسبية جزء هام من نظام المعلومات الإداري الذي تكمله نظمه الفرعية الأخرى بعضها البعض من خلال عملها بصورة متبادلة، حيث يجب أن تتوفر هذه المعلومات بشروط و خصائص معينة في جميع مراحل عملية اتخاذ القرار وذلك للوصول إلى قرارات ذات جودة ومنفعة." "This study aims to know how accounting information systems contribute to improving the decision-making process by identifying accounting information systems and all its parts, through the decision-making process, and to determine the extent to which accounting information systems contribute and their role in improving the stages of the decision-making process in the economic institution. One of the most important results reached is that accounting information systems represent the basic and important part of management information systems in economic institutions, which in turn collect various financial data from sources outside and inside the institution and then operate this data and transform it into financial data that is useful for making decisions and providing it to internal and external users ,Accounting information systems are an important part of a management information system whose other subsystems complement each other through their mutual functioning. This information must be available under certain conditions and characteristics at all stages of the decision-making process in order to reach decisions of high quality and benefit."
مذكرة ماستر